Models and Technologies for Smart, Sustainable and Safe Transportation Systems - de Luca, Stefano; Di Pace, Roberta; Fiori, Chiara (IntechOpen, 2021)
Innovative and smart mobility systems are expected to make transportation systems more sustainable, inclusive, and safe. Because of changing mobility paradigms, transport planning and design require different methodological approaches. Over twelve chapters, this book examines and analyzes Mobility as a Service (MaaS), travel behavior, traffic control, intelligent transportation system design, electric, connected, and automated vehicles, and much more.